Polysulfone with Different Degrees of Sulfonation: Simple Method with Acetyl Sulfate - de Souza, Altamiro Xavier; Frighetto, Paulo Donato; Badagnani de Carvalho, Gabriel; de Castro Degiovani, Henrique; Firmino de Oliveira , Marcelo; Neri, Cláudio Roberto; Palaretti, Vinícius; de Faria , Anizio Marcio; Pasquini, Daniel; de Morais , Luís Carlos (Orbital: The Electronic Journal of Chemistry, 2024)
In this work, the authors present as an innovation, the homogeneous sulfonation of Udel® polysulfone (PSU) with acetylsulfate (ACS) under reflux at 45°C in dichloromethane and inert N2 atmosphere (g) for 1.5 h. Different proportions of ACS were used, obtaining sulfonated products with varying degrees of sulfonation (DS). Confirmation of sulfonated polysulfone (PSU-S), denominated as PSU-SA (high degree of sulfonation) and PSU-SB (low degree of sulfonation), was carried out by FTIR and 1H NMR. Determination of DS was carried out through thermogravimetric analysis (TGA/DSC), varying indexes between 0.883 and 3.022, which correspond to a sulfonated polymer with ion exchange capacity (IEC) from 1.720 to 4.400 meq/g. The evolution of DS related to methods used was monitored and confirmed by 1H NRM. Sulfonation is undertaken to enhance the suitability of this polymer for future applications in the production of biofuels, targeting its utilization in catalytic processes for esterification and transesterification mechanisms of oils and fats.